Patient Safety and Hospital-Based Health Promotion in Preventing Infections and Their Impact on Childhood Stunting: A Systematic Review - Jasmin Ambas; Yasinta Indah Widyaningsih (Journal of Epidemiology and Public Health, 2025)
Background: Child stunting is influenced by nutrition, recurrent infections, and the quality of health services. Patient safety and hospital-based health promotion play key roles in preventing infections that increase stunting risk. This study aimed to analyze the role of patient safety and hospital-based health promotion in infection prevention and its impact on childhood stunting. Subjects and Method: A systematic review was conducted following the PRISMA guidelines and the PICO framework. The Joanna Briggs Institute (JBI) Checklist was used for quality assessment. Articles were collected from Scopus, ScienceDirect, ProQuest, SpringerLink, Google Scholar, Nature, JSTOR, and Emerald Insight, covering publications from 2020 to 2025. The keywords used were: “patient safety” AND “hospital-based health promotion” AND “infection prevention” AND “childhood stunting”, and “hospital governance” AND “infection control” AND “child growth”. Boolean operators and Medical Subject Headings (MeSH) were applied to each database. Results: This systematic review consisted of 10 articles that met the inclusion criteria. The studies, published between 2020 and 2025, originated from Indonesia, Ethiopia, Southeast Asia, and other developing regions. The findings showed that patient safety programs and infection control effectively reduced neonatal and childhood infections. Health promotion interventions, such as caregiver education and cadre training, improved hygiene and preventive behavior. Integration of hospital governance and policy strengthened infection prevention and service quality. Across the reviewed evidence, exposure to infection during the first 1,000 days of life was consistently linked to an increased risk of stunting (OR=1.85; 95% CI=1.42–2.37; p=0.001). Conclusion: Patient safety and hospital-based health promotion are crucial for preventing infections and reducing stunting. Strengthening hospital governance through integrated infection prevention strategies is essential to accelerate stunting reduction.